Structures of the methyltransferase component of Desulfitobacterium hafniense DCB‐2 O‐demethylase shed light on methyltetrahydrofolate formation. (1st September 2015) - Sjuts, Hanno; Dunstan, Mark S.; Fisher, Karl; Leys, David
<x xml:space="preserve">Abstract</x> O‐Demethylation by acetogenic or organohalide‐respiring bacteria leads to the formation of methyltetrahydrofolate from aromatic methyl ethers. O‐Demethylases, which are cobalamin‐dependent, three‐component enzyme systems, catalyse methyl‐group transfers from aromatic methyl ethers to tetrahydrofolate via methylcobalamin intermediates. In this study, crystal structures of the tetrahydrofolate‐binding methyltransferase module from a Desulfitobacterium hafniense DCB‐2 O‐demethylase were determined both in complex with tetrahydrofolate and the product methyltetrahydrofolate. While these structures are similar to previously determined methyltransferase structures, the position of key active‐site residues is subtly altered. A strictly conserved Asn is displaced to establish a putative proton‐transfer network between the substrate N5 and solvent. It is proposed that this supports the efficient catalysis of methyltetrahydrofolate formation, which is necessary for efficient O‐demethylation.